A Review of Research on Environmental Issues in the Logistics Industry - Lin, Chieh-Yu (Information Management and Business Review, 2011)
The logistics industry plays an important role in the global supply chain system. While environmental issues have become critical concerns all over the world, there is a challenge for logistics practitioners and academics to include environmental issues in logistics operations. However, scant attention was paid to environmental issues in the logistics industry. This article aims to understand the trends, gaps, and research opportunities of environmental issues in the logistics industry. Reviewing related literature suggests three broad research areas: the substance of environmental logistics practices, the determinants of environmental logistics practice adoption, and the consequences of implementing environmental logistics practices. Advice for logistics practitioners and opportunities of future research for academics are discussed.